Lessons Learned from an LGBTQ Senior Center: A Bronx Tale. Issue 7 (16th November 2016) - McGovern, Justine; Brown, Dwayne; Gasparro, Vita
ABSTRACT: This article describes an interdisciplinary pilot study exploring the impact of LGBTQ senior centers on the lives of center members. Many LGBTQ adults face the future having experienced stigma and bias, restricted rights, and rejection from family of origin, and are now growing older without the support of a partner and adult children. As a result, older LGBTQ adults experience higher rates of depression, loneliness and isolation, and shortened life expectancy as compared to non-LGBTQ peers. Findings from focus group and key informant interviews highlight features of LGBTQ senior center experiences that can significantly improve members' quality of life. These include providing family, acceptance and a home, which can have an impact on outlook and outcomes. Moreover, findings suggest the need for re-thinking hetero-normative definitions of "community" in the context of LGBTQ aging. Beyond sharing findings from the study, suggesting a conceptual framework for deepening understanding about LGBTQ aging, and identifying lines of future inquiry, the article articulates implications for social work research, practice and education. Ultimately, the article argues that social work is well positioned to improve quality of life for this under-served population when it adopts a cultural humility stance in research, practice and education.